Kedudukan Lembaga Negara Independen Berfungsi Quasi Peradilan dalam Sistem Ketatanegaraan Indonesia - Eki Furqon (Nurani Hukum, 2020)
The development of the concept of state institutions has given rise to the idea of creating an independent state institution that has a quasi-judicial function, aiming to maximize the expected achievements by taking into account that an independent state institution is a state institution that is free from intervention from other parties. However, the quasi-judicial function in independent state institutions is not fully equal or equal to the function in state institutions which are under the branch of judicial power. For this reason, this paper was made with the aim of seeing how the position of an independent state institution functions as a quasi-judicial system in the Indonesian constitutional system.The method used in this research is descriptive qualitative using library data as the main data. The author uses normative juridical research methods with due regard to existing legal rules and is directly related to the research topic this time.Research results show that, an independent state institution that functions as a quasi-judiciary has a foothold in the constitution in Article 24 Paragraph (3) which means that the constitution requires the existence of a state institution outside the state institution in the judicial branch of power to participate in the judicial function as long as it is regulated by law . Independent state institutions function as a quasi-judicial system such as the KPPU, KPI, Information Commission, Bawaslu, and the Ombudsman in their arrangements to have the authority to settle cases or disputes in their respective fields, which means there is a quasi-judicial function within these institutions.Perkembangan konsep kelembagaan negara telah melahirkan ide penciptaaan lembaga negara independen yang memiliki fungsi quasi peradilan, bertujuan untuk memaksimalkan capaian yang diharapakan dengan memperhatikan bahwa lembaga negara independen adalah lembaga negara yang terbebas dari intervensi pihak lain. Meskipun demikian, fungsi quasi peradilan yang ada dalam lembaga-lembaga negara independen tidak sepenuhnya setara atau sama dengan fungsi yang ada pada lembaga negara yang berada dibawah cabang kekuasaan yudikatif. Untuk itu, tulisan ini dibuat dengan tujuan untuk melihat bagaimana kedudukan lembaga negara independen berfungsi quasi peradilan dalam sistem ketatanegaraan Indonesia.Metode yang digunakan pada penelitian ini bersifat kualitatif deskriptif dengan menggunakan data kepustakaan sebagai data utama. Penulis menggunakan metode penelitian yuridis normatif dengan memperhatikan aturan hukum yang ada dan berkaitan langsung dengan topik penelitian kali ini.Hasil Peneltitian menunjukan bahwa, lembaga negara independen berfungsi quasi peradilan memiliki pijakan pada konstitusi pada Pasal 24 Ayat (3) yang mana bermakna bahwa konstitusi menghendaki adanya lembaga negara diluar daripada lembaga negara dalam cabang kekuasaan yudikatif untuk turut memiliki fungsi mengadili sepanjang diatur dengan undang-undang. Lembaga negara independen berfungsi quasi peradilan seperti KPPU, KPI, Komisi Informasi, Bawaslu, dan Ombudsman dalam pengaturannya memiliki kewenangan untuk melakukan penyelesaian perkara atau sengketa yang ada di masing-masing bidangnya yang berarti terdapat fungsi quasi peradilan di dalam lembaga-lembaga tersebut.